2022
DOI: 10.1002/emp2.12792
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of emergency department throughput and process times between male and female patients: A retrospective cohort investigation by the Reducing Disparities Increasing Equity in Emergency Medicine Study Group

Abstract: Introduction:Health equity for all patients is an important characteristic of an effective healthcare system. Bias has the potential to create inequities. In this study, we examine emergency department (ED) throughput and care measures for sex-based differences, including metrics such as door-to-room (DTR) and door-to-healthcare practitioner (DTP) times to look for potential signs of systemic bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(24 reference statements)
0
0
1
Order By: Relevance
“…Additionally, this increase is mainly due to the higher use of PM in women (20% of increase), while use of NSAID and opiates seems to be more balanced among sexes. The results obtained in this study are in contrast to those obtained in younger populations, in which a lower frequency of analgesic prescription has been observed in women [16]. Therefore, a line of further investigation specifically designed to address if sex-based inequality in use analgesics in EDs is clearly needed.…”
Section: Discussioncontrasting
confidence: 91%
“…Additionally, this increase is mainly due to the higher use of PM in women (20% of increase), while use of NSAID and opiates seems to be more balanced among sexes. The results obtained in this study are in contrast to those obtained in younger populations, in which a lower frequency of analgesic prescription has been observed in women [16]. Therefore, a line of further investigation specifically designed to address if sex-based inequality in use analgesics in EDs is clearly needed.…”
Section: Discussioncontrasting
confidence: 91%
“…Previous studies have suggested that the patient's sex influences the access to healthcare and the quality of care provided, from the out-of-hospital environment to specialized inpatient treatments [6]. For instance, significant sex disparities in time-sensitive emergencies such as cardiac care have been reported, suggesting that females are less likely to undergo extensive cardiac workup [7][8][9][10][11][12][13] and to receive cardiac treatment such as aspirin, nitroglycerin and IV access [14] and cardiac catheterization after myocardial infarction [15], resulting in worse outcomes overall [9]. Furthermore, females are less likely than males to be admitted to an intensive care unit [6,8] and to receive intravenous tissue plasminogen activator for a stroke [16].…”
Section: Introductionmentioning
confidence: 99%